MECHANISM OF STRUCTURAL GEOLOGY DEVELOPMENT AND THEIR EFFECT TO HIDROCARBON TRAPPING IN KUANG HIGH, SOUTH SUMATRA BASIN - TRIWERDHANA, AFRIADHI
Development of geological structure in Kuang High was influenced by regional tectonics in South Sumatra Basin. Structural development has been controled the hydrocarbonÃ‚Â’s trapping mechanism. There are several questions in hydrocarbon exploration at Kuang High area, especially which are related with the structural geology aspect: How structural pattern around that area should be? Are the local patterns similar with the regional pattern? Are their structural development influenced by a specific mechanism? Which lithologies unit infected by the stress force in this area? How about stress direction? And how do the stress controled the hydrocarbon trapping? Subsurface structure has been interpreted using seismic 3D and shown existing fault and fold configuration. Fault orientation is NE-SW and fold orientation is NW-SE. Isopach map from several horison shown the structural configuration at Oligo-Miosen, Mid Miosen and Plio-Plistosen. FMI data used to predict the dominan stress using strain analysis to describe ?1, ?2, ?3. Integrated structural analysis including descriptive, kinematic, and dynamic have been done to describe structural pattern, strain and stress in Kuang High area. Palinspatic restoration has been done to calculate strain. This study result shown that the local deep in Oligo-Miosen have common orientation of the grabens pattern to NW-SE (N300o-330oE), and the lineanment of major fault have orientation to WSW-ENE (N230o-260oE). Then in the Middle Miosen, fold axis have orientation to NW-SE (N300o-330oE) and the minor fault orientation to NE-SW (N40o-50oE). In the Plio-Pleistocene, wrenching system has been continued through the major fault WSW-ENE (N230o-260oE) and development of fold has been developed with the orientation to NW-SE (N300o-330oE). Strain analysis shown that the area was shortened at NE-SW direction which is correlated with the stress orientation of N-S dan NE-SW. With the assumption that the peak of hydrocarbon maturity in the Middle Miocene, then we can know that the migration pattern and trap mechanism in the area. At least five migration pathways present in Kuang area, hydrocarbon migrated from the kitchen and trapped in nearest structures, there are : from Lematang Deep to Tasim-Pagardewa structure, from Muara Enim Deep to Prabumenang structure, from Pemaat Deep to Kuang High, from Lematang Deep to Beringin-North Kuang and Kuang and from Jantung Deep to Kuang structure.